2020
DOI: 10.1155/2020/8438272
|View full text |Cite
|
Sign up to set email alerts
|

Inner Engineering Practices and Advanced 4‐day Isha Yoga Retreat Are Associated with Cannabimimetic Effects with Increased Endocannabinoids and Short‐Term and Sustained Improvement in Mental Health: A Prospective Observational Study of Meditators

Abstract: Background. Anxiety and depression are common in the modern world, and there is growing demand for alternative therapies such as meditation. Meditation can decrease perceived stress and increase general well-being, although the physiological mechanism is not well-characterized. Endocannabinoids (eCBs), lipid mediators associated with enhanced mood and reduced anxiety/depression, have not been previously studied as biomarkers of meditation effects. Our aim was to assess biomarkers (eCBs and brain-derived neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…COVID-19-related stress creates panic and reduces quality of life in patients as well as in healthcare workers (HCWs). Hence, introducing Yoga in the healthcare system would be beneficial for the patients, HCWs, and other service providers: they may successfully cope with psychological stress (34)(35)(36)(37). Stress, anxiety, and depression among HCWs in COVID-19 pandemic was reduced by practicing Sudarshan kriya (38).…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19-related stress creates panic and reduces quality of life in patients as well as in healthcare workers (HCWs). Hence, introducing Yoga in the healthcare system would be beneficial for the patients, HCWs, and other service providers: they may successfully cope with psychological stress (34)(35)(36)(37). Stress, anxiety, and depression among HCWs in COVID-19 pandemic was reduced by practicing Sudarshan kriya (38).…”
Section: Discussionmentioning
confidence: 99%
“…Other theoretical models hypothesize that mindful meditation can restructure the pain-related cognitive content, making adaptive changes necessary to counter pain perception. Studies have shown an increase in the EC levels even after short-term meditation practice, providing evidence of the analgesic potential of mindbody therapies (Sadhasivam et al, 2020). Understanding and individualizing the treatment and matching it to the patient's requirement can improve treatment response, adherence, and outcomes (Day et al, 2020;Zetterqvist et al, 2020).…”
Section: Non-pharmacological Therapiesmentioning
confidence: 99%
“…Although many studies have examined depression and ω3 PUFAs, studies examining the association between ω3 PUFAs and happiness are sparse. However, studies concerning depression are beneficial for discussions of happiness because endocannabinoids (eCBs) may also act on the remission of depression [ 31 , 32 ]. eCBs are an important class of biologically active FA-derivatives, which have been identified as cannabinoids or a cannabis-like compound [ 10 ].…”
Section: Discussionmentioning
confidence: 99%